Development of methods for the gas chromatogrphic determination of the content of dissolved components in the energy oils - Зайцев, Сергей Владимирович; Кишневский, Виктор Афанасьевич; Савич, Святослав Лаврентьевич (Eastern-European Journal of Enterprise Technologies, 2014)
The paper presents the results of the development of methods for the gas chromatographic determination of the content of dissolved components: gases (H2, CH4, C2H6, C2H4, C2H2, CO, CO2, C3H8, C3H6, H2S); ionol; furan compounds (furfural; acetylfuran; 5-methyl-furfural; 2-furan-methanol) in the energy oils (transformer, cable, condenser, turbine). The purpose of the paper was to reduce the errors of measurement methods and improve the accuracy of measurement results in determining the content of dissolved components in the energy oils by the static version of the extraction-gas chromatographic measurements using gas chromatographic analysis of equilibrium phases - gaseous or liquid extracts. For modern energy oils, the values of the distribution coefficients in the system "energy oil - dissolved gas - gas-extractant" using static and dynamic variants of extraction-gas chromatographic measurements were defined; formulas for calculating the concentrations of ionol and furan compounds in the energy oils based on accepted mathematical models of extraction processes for measurements were obtained; optimum procedures of extraction-gas chromatographic determination of the content of dissolved gases, ionol and furan compounds in the energy oils for developing optimal gas scheme of multichannel gas chromatograph were selected. The conditions for implementing the extraction-gas chromatographic measurements using appropriate adsorbents in packed chromatographic columns in determining the content of: dissolved gases - by the absolute calibration using the distribution coefficients for these gases instead of the corresponding Ostwald coefficients; ionol or furan compounds - by adding corresponding pure component or various extractant volumes in the energy oils. In the presence of emulsion water in the energy oil, oil is dried by silica gel (in determining ionol) or sodium sulfate (in determining furan compounds. The results of the calculations are assessed). It was found that it is necessary to perform temperature programing of the corresponding chromatographic column after the evolution of the chromatographic peak of the last determined component. The developed techniques can be used in determining the concentrations of dissolved components in the energy oils for technical diagnostics of oil-filled electrical equipment; quality indicators of the energy oils; compatibility of mixed energy oils and sensitivity of these oils to ionol.